Konstruksi Diri dan Pengelolaan Kesan pada Ruang Riil dan Ruang Virtual - Benedictus A. Simangunsong (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2010)
The development of technology, especially in media, has affected the form of self and interaction in everyday life. In real life situation, humans actually have face to face interactions and they can see others’ given and given-off behaviors. However, when the internet becomes one of the tools for interaction with others, a different forms of self and interaction emerge. It means we are doing an interaction in the mediated world which we call as interpersonal mediated communication. In this era, we do not know exactly the kind of people we communicate with, so one of ways to know about others is from the impression they give us; which is call a front stage. In this paper I introduce how the dramaturgical concept, especially the Impression Management, from Erving Goffman can be used to describe how people interact in the virtual world.